2021
DOI: 10.1001/jamapediatrics.2020.6069
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Feasible Specimen Collection and Testing Strategies for Diagnosing Tuberculosis in Young Children

Abstract: IMPORTANCE Criterion-standard specimens for tuberculosis diagnosis in young children, gastric aspirate (GA) and induced sputum, are invasive and rarely collected in resource-limited settings. A far less invasive approach to tuberculosis diagnostic testing in children younger than 5 years as sensitive as current reference standards is important to identify.OBJECTIVE To characterize the sensitivity of preferably minimally invasive specimen and assay combinations relative to maximum observed yield from all specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 27 publications
1
38
0
2
Order By: Relevance
“…Collecting samples of different types, particularly including samples that are less invasive and easier to implement from a technical point of view, may significantly contribute to increasing the yield of microbiological testing. In the same study of children with presumptive TB in Kenya, combining one NPA and one stool increased the sensitivity to 71% compared to 66% for one NPA specimen, with results similar to what was obtained using two GA or two sputum samples [85]. Similarly, in another international diagnostic accuracy study in HIV-positive children with presumptive TB from four high-incidence countries, Xpert testing of one NPA and one stool increased sensitivity from 69% for NPA only and 62% for stool only, to 75% when using both [62].…”
Section: Combining Samplessupporting
confidence: 65%
See 1 more Smart Citation
“…Collecting samples of different types, particularly including samples that are less invasive and easier to implement from a technical point of view, may significantly contribute to increasing the yield of microbiological testing. In the same study of children with presumptive TB in Kenya, combining one NPA and one stool increased the sensitivity to 71% compared to 66% for one NPA specimen, with results similar to what was obtained using two GA or two sputum samples [85]. Similarly, in another international diagnostic accuracy study in HIV-positive children with presumptive TB from four high-incidence countries, Xpert testing of one NPA and one stool increased sensitivity from 69% for NPA only and 62% for stool only, to 75% when using both [62].…”
Section: Combining Samplessupporting
confidence: 65%
“…However, this was a conditional recommendation, with a low certainty of evidence in test accuracy for sputum and very low for other specimens [8]. In a study of 300 children with presumptive TB aged <5 years in Kisumu, Kenya, testing a second sample of the same kind (GA, NPA, or IS) led to an average incremental yield of 8% to 10% by Xpert or MGIT, respectively [85]. A systematic review reported that testing a second sample contributes between 6% and 33% of the cumulative microbiological yield using Xpert or culture, regardless of the sample collection method [65].…”
Section: Combining Samplesmentioning
confidence: 99%
“…However, the detection of S. pneumoniae by PCR ( lytA ) in culture negative blood [ 93 , 94 ] and lung aspirate [ 24 ] specimens is not universally regarded as diagnostic of pneumococcal pneumonia in children, as detection by PCR may reflect carriage rather than disease. Nasopharyngeal aspirate can be used to detect M.tuberculosis, especially given the increasing availability of Xpert MTB/RIF [ 95 ]. In children with respiratory distress, the use of sampling such as nasopharyngeal aspirate or stool has advantages over more invasive sampling such as induced sputum or gastric aspirate [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in adults, sputum-based reference tests are often not appropriate in young children. Microbiological reference standards based on combinations of alternative samples such as gastric or nasopharyngeal aspirates are therefore recommended ( 68 ). To ensure comparability of results across studies, classification of children should conform to the National Institutes of Health consensus definitions for childhood pulmonary tuberculosis (i.e., confirmed, unconfirmed, and unlikely TB) ( 69 ).…”
Section: Discussion: Potential In Children and Future Directionsmentioning
confidence: 99%